Star wars : sanctuary - Giles, Lamar, 1979- (Random House Worlds, 2025)
"Hunter, Wrecker, Tech, and Omega gamble on a mission to help rebuild Pabu in this thrilling adventure for The Bad Batch. A good soldier knows that life is all about change-whether it's on or off the battlefield. Surviving, living, means adaptation. Hunter is well acquainted with this lesson. He's on the run from the Empire, Echo's off on a mission with Captain Rex, and Crosshair is . . . still Crosshair, but amidst all the change, Hunter still has Tech, Wrecker, and Omega. And it seems that his small family might have finally found a safe place to land, far from the increasingly vigilant eyes of the Empire: Pabu. But their potential new island home is in desperate need of resources if there is any hope for the fledgling community to recover from a devastating sea wave. That's where Phee Goena, self-proclaimed liberator of treasures, comes in, with a couple of jobs she swears will get them the funds they need. Despite Hunter's concern with Phee's precarious plans, the rest of the crew is fine following her lead. Things go wrong almost immediately, as Phee's droid blows the crew's cover at a high-stakes auction, and they barely make it out with the relic they'd been paid to acquire. Hunter insists they finish their first mission and deliver the relic before taking on more work, but Phee and the others push forward with a second job: ferrying a couple on the run, one of whom is due to give birth at any moment. Hunter worries that they're risking too much, especially when their mysterious new passengers cling to lies and secrets that trace back to an Imperial Security Bureau officer hot on their trail. As Hunter tries to get the crew back on a stable, safe path far, far away from anything to do with the Empire's watchdogs, their overlapping missions only invite more danger and chaos. On the verge of failing both their desperate passengers and their community on Pabu, the Batch must remember that the only way they succeed, the only way they survive to fight another day, is by trusting each other."--